2018
DOI: 10.2147/dhps.s158592
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of medicinal marijuana: an educational primer for health care professionals

Abstract: With the proposed Canadian July 2018 legalization of marijuana through the Cannabis Act, a thorough critical analysis of the current trials on the efficacy of medicinal marijuana (MM) as a treatment option is necessary. This review is particularly important for primary care physicians whose patients may be interested in using MM as an alternative therapy. In response to increased interest in MM, Health Canada released a document in 2013 for general practitioners (GPs) as an educational tool on the efficacy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 227 publications
(253 reference statements)
0
41
0
7
Order By: Relevance
“…This is consistent with prior research showing knowledge deficits surrounding medical cannabis for practicing clinicians as well as in medical residents. [14][15][16][17][18][19] This has implications for a primary care workforce that is increasingly likely to encounter patients seeking clinical guidance regarding medical cannabis. Regardless of a particular state's legality of cannabis, the overall momentum of cannabis use in the United States is trending toward increased use and overall acceptance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with prior research showing knowledge deficits surrounding medical cannabis for practicing clinicians as well as in medical residents. [14][15][16][17][18][19] This has implications for a primary care workforce that is increasingly likely to encounter patients seeking clinical guidance regarding medical cannabis. Regardless of a particular state's legality of cannabis, the overall momentum of cannabis use in the United States is trending toward increased use and overall acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Despite this, educational resources for family physicians are clearly lacking. [14][15][16][17][18][19] While one might assume that physicians in states with a longer history of available medical cannabis would have curriculum around this topic, this is currently unknown. To complicate decisions regarding educational needs, 43% of residents will practice in a state different to where they have completed their training, which may necessitate cannabis training despite local laws.…”
Section: Original Articlesmentioning
confidence: 99%
“…For example, the international open access journal "Drug, Healthcare and Patient Safety" published a review dealing with the evidence-based analysis of the cannabinoid therapeutic potential; the authors stated that cannabinoids are a suitable alternative to classical treatments for patients suffering from epilepsy, movement disorders, and pain. As a further possible choice are mentioned patients with multiple sclerosis, digestive tract disorders, anorexia, and multiple myeloma [48].…”
Section: Endocannabinoidome In Health and Disease And The Therapeutimentioning
confidence: 99%
“…For several years cannabidiol, CBD, a constituent of Cannabis sativa without psychotropic effects, has been empirically used as an anti-inflammatory drug and modulator of cancer progression. Recent studies highlighted that CBD is toxic at different concentrations in diverse cells, making the results obtained in cell models and the clinic difficult to interpret and, therefore, for defining the proper dose for patients [8]. On the other hand, in vitro studies have shown that activation of the cannabinoid receptors modulates different steps of tumorigenesis in several types of cancer [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…These reports have suggested that CBD has a potential role in the treatment of tumors and chronic inflammatory diseases. Therefore, a better understanding of the cellular and molecular mechanisms underlying CBD activities is imperative for its safe administration in patients, particularly when treatment is prolonged [8,13].…”
Section: Introductionmentioning
confidence: 99%